THE DYNAMICS OF INTERNAL AND EXTERNAL FACTORS IN SHAPING INTEREST IN SHARIA INVESTMENT IN CIAMIS REGENCY - Acim Acim; Achmad Zaki Fadhil (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2026)
This research aims to analyze the influence of internal and external factors on sharia investment decisions in Ciamis Regency. Internal factors include financial literacy, investment experience, and religiosity, while external factors consist of economic conditions, government policies, and social environment. The research uses a quantitative approach with a sample of 100 respondents selected through purposive sampling. Data were analyzed using multiple linear regression. The findings indicate that internal and external factors significantly influence investment decisions with a negative direction, suggesting that increased capacity and information intensity lead to higher levels of prudence among investors in Ciamis. These results imply that the regional government and sharia financial institutions need to provide more applicable and simplified education to convert this cautious attitude into real investment participation while maintaining the values of prudence in the local urban-religious society.